‘I Live a Kind of Shadow Life’: Individual Experiences of COVID-19 Recovery and the Impact on Physical Activity Levels - James Shelley (MDPI AG, 2021)
Understanding of strategies to support individuals recovering from coronavirus disease 2019 (COVID-19) is limited. ‘Long COVID’ is a multisystem disease characterised by a range of respiratory, gastrointestinal, cardiovascular, neurological, and musculoskeletal symptoms extending beyond 12 weeks. The aim of this study was to explore individuals’ experiences of recovering from COVID-19 to provide a better understanding of the acute and long-term impact of the disease on physical activity (PA). Individualised semi-structured interviews were conducted with 48 adults recovering from COVID-19 at 6–11 months post-infection. An inductive thematic analysis approach was used, reaching saturation at 14 interviews (10 female; 47 ± 7 years). Four overarching themes were identified: (i) Living with COVID-19, including managing activities of daily living; (ii) Dealing with the Unknown and self-management strategies; (iii) Re-introducing physical activity; and (iv) Challenges of returning to work. The return to PA, whether through activities of daily living, work or exercise, is often associated with the exacerbation of symptoms, presenting a range of challenges for individuals recovering from COVID-19. Individually tailored support is therefore required to address the unique challenges posed by COVID-19.